Bones. The complete second season [videorecording (DVD)] - Taylor, Tamara; Boreanaz, David, 1971-; Conlin, Michaela; Deschanel, Emily; Millegan, Eric; Thyne, T. J. (20th Century Fox Home Entertainment, 2007)
Forensic anthropologist Dr. Temperance "Bones" Brennan and FBI Special Agent Seely Booth combine her uncanny ability to decipher clues found in the remains of victims and his hard-hitting investigative techniques. The two use state-of-the-art forensic technology to solve some of the most baffling and bizarre crimes ever. Brennen gets a new boss and takes on a new partner, tensions mount, passions flare and a shocking conspiracy forces her to confront her troubled past.